Numerical Analysis of Structural Performance of Concrete-GFRP Composite I-Beam - Chen, Zhaohui; Xing, Jiajie; Luo, Qiwen; Zhang, Xiaoyue (Frontiers in Materials, 2022)
GFRP-concrete composite beams have drawn widely interest in civil engineering. However, the indistinction of the procession for fracture and debonding of the interface and GFRP profile has limited the accurate design of the composite beam. This paper presents comprehensive numerical investigations about the structural performance of composite pultruded GFRP beams in order to improve the understanding of the mechanism of debonding of the interface and the fracture of the GFRP matrix. The failure and delamination process of the pultruded GFRP regarding the material’s anisotropy is modeled using Hasin criteria. The bond-slip behavior between the concrete slab and the top flange of the GFRP I-beam is simulated by the bilinear cohesive interfacial element. The availability and accuracy of the FE model are approved by comparison with the results of four-point bending tests of pure GFRP I-beam and composite beam as well. Based on the proposed comprehensive FE model, the effects of the strength, thickness, width of concrete slab, and shear span ratio on the structural behavior of the composite beam are studied. According to the parametric analysis, the excessive strength of concrete, the width and/or thickness of the concrete slab would lead to shear failure of the slab instead of improving the ultimate load of the composite beam significantly. With a small shear span ratio, matrix fracture and delamination of the GFRP web would occur. In addition, the web height of the I-profile has a significant effect on the stress and strain distribution of the composite beam. These parametric analyses can provide the numerical basis for the design of the GFRP composite beams.